Current situation of exchanges between Korea and Vietnam on culture and higher education – Orientations and solutions - Pham, Thị Thùy Linh; Nguyen , Văn Quang; Dao, Duy Tùng (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Vietnam and Korea are two East Asian countries with many similarities in history and culture. Vietnam is in Southeast Asia, South Korea is in Northeast Asia but both countries are strategically located on a peninsula connected to the mainland and overlooking the ocean. This peninsula and ocean location also creates many close geocultural conditions of the two countries. On the other hand, In their long history of survival and development, the two countries have many times faced with the invasion of many powerful forces. That history of struggle against foreign aggression has forged the patriotic spirit and deep national consciousness of the people of each country. Over the years of hardship, Vietnam and Korea have rebuilt and developed the country on the ruins of the war. Within the framework of the article, we will highlight and analyze the current situation of cultural exchange and higher education in the two countries, thereby giving some orientations and solutions to further raise the level of comprehensive cooperation in the field of culture - Education is one of the important factors to help the Governments and peoples of the two countries understand each other better, raise the level of comprehensive strategic partnership, and open a new, higher and deeper cooperation chapter between the two countries in the context of the current situation. new scene.